Seleksi Spermatozoa Pada Fertilisasi In Vitro (IVF) - Amalia Shari (Indonesian Journal of Health Science, 2022)
In Vitro Fertilization  (IVF) is the penetration of ovum cells by spermatozoa in a culture system and is a reproductive technique that is useful for increasing the efficiency of sperm and ovum utilization. In vitro fertilization is applied to overcome the problem of infertility and prevent of birth defects. The success of IVF is influenced by the quality of spermatozoa. In order to fulfill this, it is necessary to select spermatozoa, which is to separate good quality spermatozoa from the total population. Spermatozoa selection can be done by knowing the quality of spermatozoa which consists of spermatozoa morphology, spermatozoa motility, and spermatozoa concentration. Spermatozoa selection can also be seen by measuring DNA sperm damage. Various tests have been developed to measure DNA sperm damage, such as acridine orange staining test, SCSA, Comet and TUNEL assay. Fertilisasi in vitro (In Vitro Fertilization) merupakan penyatuan sel ovum dengan spermatozoa dalam suatu sistem kultur dan merupakan salah satu Teknik reproduksi yang bermanfaat untuk meningkatkan efisiensi pemanfaatan spermatozoa serta ovum. Fertilisasi in vitro (IVF) diterapkan untuk mengatasi persoalan infertilitas serta pencegahan terhadap kelahiran bayi cacat. Keberhasilan IVF salah satunya ditentukan oleh kualitas spermatozoa, dalam rangka memenuhi hal tersebut perlu dilakukan seleksi spermatozoa, yaitu memisahkan spermatozoa berkualitas baik dari total populasi. Seleksi spermatozoa dapat dilakukan dengan mengetahui kualitas spermatozoa yang terdiri dari morfologi spermatozoa, motilitas spermatozoa dan konsentrasi spermatozoa. Seleksi spermatozoa dapat ditinjau juga menggunakan pengukuran kerusakan DNA sepermatozoa. Berbagai tes telah dikembangkan untuk mengukur kerusakan DNA spermatozoa, seperti tes pewarnaan acridine orange, SCSA, Comet, serta TUNEL assay.